Differentiation of RVOT-VT and ARVC in an elite athlete - Whyte, G. P.; Stephens, N.; Senior, R.; Peters, N.; O'Hanlon, R.; Sharma, S. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Background: Differentiation of right ventricular outflow tract-ventricular tachycardia (RVOT-VT) and arrhythmogenic right ventricular cardiomyopathy (ARVC) can be problematic in athletes. The high incidence of sudden death as the first clinical manifestation in ARVC highlights the importance of correct diagnosis and treatment. We report on the case of RVOT-VT in an elite female sprinter, and we review the literature on ventricular tachycardia (VT) in the absence of structural heart disease and ARVC.